Teaching English for Specific Purpose Through a Book Entitled “Communicating at Work: Principles and Practices for Business and the Professions” - Ariani Rosadi; Lubis Hermanto (Journal on Education, 2023)
This study aims to investigate the experience of teaching ESP (English for Specific Purpose) courses for students of the communication science study program at Mbojo Bima University. Dominantly, ESP teaching uses an English book entitled "Communicating at Work". This book was written by Ronald B. Adler and Jeanne Marquardt Elmhorst and was printed in the fifth edition and published by The McGraw Hill Companies. The subtitle of this book reads "principles and practices for business and the professions". Researchers use Narrative research to describe the knowledge of teachers. One of the campuses that uses this book is Mbojo Bima University and in the view of researchers it is very suitable for the needs of communication science students as a reference for ESP courses. Teaching with this book reflects the life of the work career. There are several descriptions of the reviews contained in it, including materials on how to communicate in the world of work involving cultural aspects, language skills and strategies for dealing with the world of work. The weakness of this book is that the use of English is at an intermediate level. However, overall ESP teaching books using this book are very helpful in explaining ESP concepts. The basic things about English in general have been taught in the previous semester and this ESP course is used as a complement.